CUCUPATIAN (TEKA-TEKI) BANJAR: ANALISIS STRUKTUR, FUNGSI, DAN NILAI BUDAYA - Rustam Effendi (Masyarakat Indonesia, 2010)
Results of an early observation show that cucupatian (riddles), one of the pillars of the Banjar culture has been ignored by the Banjar communities and is now in the brink of extinction. To confirm the findings, the research uses the qualitative approach where the researcher functions as a human instrument. The research uses the theory of transformation generative-grammar, a theory of folklore (a theory that pertains to the structure of folklore, and functions as well as cultural values), and a theory of pragmatics. The main location of the study is Kota Banjarmasin, Kabupaten Hulu Sungai Utara, and Kabupaten Hulu Sungai Tengah. The data collection was carried out by using a participant-observation method and in-depth interviews. The research commenced with four Banjarian culturalists. From two informants, information about other informants who knew cucupatian was gathered. To avoid qualms on the data that have been accumulated, the researcher tested the validity of the data by using triangulation. The analysis of the data was carried out with the methodology proposed by Miles and Huberman (1992) which begins with data reduction and continued with data presentation and the conclusion. Based on the analysis of data, this research has produced the followings: (1) Banjars cucupatian is divided into tatangguhan dan mahalabiu. (2) Tatangguhan is rooted in the traditional community while mahalabiu is rooted in the current modern society. (3) Tatangguhan is rarely found, and it can be said that it is in the brink of extinction. Todays era is the era of mahalabiu, a variation of tatangguhan which stresses on the joke aspects by using words, phrases, or sentences which are ambiguous. (4) There are five 210 | Masyarakat Indonesiafunctions of tatangguhan, which are: the knowledge system, the mediation system, the participation system, the communication system, and the practice system. From these functions, knowledge and mediation systems are more dominant in tatangguhan. (6) Cultural values of tatangguhan revolve around social values, ethics, philosophies, religions, and aesthetics, and the values of mahalabiu in addition to being social values (especially social critics) are also having religious values. (7) The structure of tatangguhan inclines not to follow the inner structure method of the Banjar language and it has a surface structure (transformation of sentences) that has 11 forms of transformation of sentences; FN+FPrep; FN+FAdj; FN+FNum; FNum+FAdj; FV+FAdj; FAdj+FV; FV+FPrep; FAdj+FAdj; FV+FN; FPrep+FPrep; FAdj+FAdj. (8) The structure of mahalabiu tends to follow the sentences inner structure of the Banjar language. Occasionally, to explain sentence information, mahalabiu is turned into a discourse. Cucupatian contains many cultural teachings. Hence, it is suggested that every societal member, in particular the local government and scholars need to strive in order to save cucupatian from extinction.Key words: cucupatian, tatangguhan, mahalabiu